RANIBIZUMAB FOR MACULAR EDEMA AFTER BRANCH RETINAL VEIN OCCLUSION: One Initial Injection Versus Three Monthly Injections. Issue 4 (April 2017) - Miwa, Yuko; Muraoka, Yuki; Osaka, Rie; Ooto, Sotaro; Murakami, Tomoaki; Suzuma, Kiyoshi; Takahashi, Ayako; Iida, Yuto; Yoshimura, Nagahisa; Tsujikawa, Akitaka
Abstract : Purpose: To compare the 12-month-efficacy of 1 initial intravitreal ranibizumab injection (IVR) followed by pro re nata (PRN) dosing with that of three initial monthly IVR followed by PRN dosing in patients with macular edema (ME) after branch retinal vein occlusion. Design: Prospective, interventional study. Methods: Of 81 eyes, 42 received 1 initial IVR injection (1+PRN group) and 39 eyes received 3 monthly IVRs (3+PRN). Pro re nata injections were performed when fovea exudative changes were evident. Results: At Month 12, the visual acuity (VA) changes from baseline were −0.245 ± 0.227 and −0.287 ± 0.222, in the 1+PRN and 3+PRN groups, respectively; there were no significant difference between groups ( P = 0.728). The stratified analysis showed that patients with better VA (baseline VA >20/40) had similar significant improvement in VA at Month 12 ( P < 0.001) to that of those with poorer VA (⩽20/40). Better VA at Month 12 was significantly associated with younger age, better baseline VA, and thinner baseline central foveal thickness ( P = 0.003, < 0.001, and < 0.001, respectively). Mean total number of IVR injections in the 1+PRN and 3+PRN groups were 3.8 ± 1.8 and 4.6 ± 1.4, respectively ( P = 0.060). In both groups, shorter durations to the first PRN injection were associated with greater total PRN injection number (1+PRN, P = 0.006; 3+PRN; group, P < 0.001). Conclusion: In IVR treatment for ME after branch retinal vein occlusion, 1+PRN and 3+PRN regimens achieved similar 12-month functional outcomes. Patients with shorter durations to initial PRN injection may require more PRN treatments. Abstract : The authors treated macular edema after branch retinal vein occlusion using either a regimen of 1 initial or 3 monthly intravitreal ranibizumab injections, and compared the Month-12 visual outcomes between the 2 groups, after enrolling patients with relatively good baseline visual acuity that any previous studies did not examine well.